Characterizing health-related quality of life and identifying disease predictors among patients suspected of having long COVID: an analysis of COMET-ICE clinical trial data - Gelhorn, Heather L.; Ghafoori, Parima; Cutts, Katelyn; Birch, Helen; Savva, Yulia; Satram, Sacha; Lloyd, Emily; Chen, Wen-Hung (Frontiers in Public Health, 2024)
Introduction: Long COVID affects health-related quality of life (HRQoL). Here, we investigate the extent to which symptoms experienced during the acute phase of COVID-19 are significant predictors of the presence of long COVID at 12 weeks. Methods: Post-hoc analysis of COMET-ICE trial data, which assessed sotrovimab vs. placebo for treatment of mild-to-moderate COVID-19 among high-risk patients. Patient-reported outcome measures were completed during the trial, including the inFLUenza Patient-Reported Outcome Plus (FLU-PRO Plus), the 12-Item Short Form (SF-12) Hybrid questionnaire, and the Work Productivity and Activity Impairment Questionnaire: General Health (WPAI:GH). COVID-19 symptoms and impacts (measured by the FLU-PRO Plus) and HRQoL (measured by SF-12 Hybrid and WPAI:GH) were compared between the acute phase (Days 1–21 and 29) and long-COVID phase (at Week 12) among patients with and without long COVID based on COMET-ICE data. Subgroups experiencing long COVID were derived using “All”, “Returning”, and “Persisting” symptomatic definitions. Long-COVID predictors were identified using a multivariate logistic regression model; odds ratios (ORs) and 95% CIs were calculated. Results: Long-COVID subgroups had significantly higher baseline scores for most FLU-PRO Plus domains and Total Score compared with the non-long-COVID group. WPAI:GH and SF-12 Hybrid scores generally showed significantly more impairment for the long-COVID subgroups at baseline and Week 12 vs. the non-long-COVID group. In the univariate analyses, all FLU-PRO Plus domains were significant predictors of long COVID (all p<0.05), with the exception of the Sense domain. Older age increased the risk of long COVID (OR 1.02, 95% CI 1.00–1.04, p<0.05). Non-White patients were significantly less likely to have long COVID by the Returning and Persisting definitions vs. White patients (all p<0.05). In the multivariate analysis, higher scores for the Nose domain (ORs 3.39–5.60, all p<0.01) and having COPD (ORs 3.75–6.34, all p<0.05) were significant long-COVID predictors. Conclusion: Patients who progressed to long COVID had higher symptom severity during the acute disease phase and showed significantly greater negative impact on HRQoL over an extended time period from initial infection through at least the subsequent 3 months. The FLU-PRO Plus Nose domain and having COPD were significant predictors of long COVID.